Escala de abuso economico: validating the Scale of Economic Abuse-12 (SEA-12) in Spanish - Johnson, Laura (Journal of family violence, 2021)
Language is a key consideration in the development of culturally-responsive interventions for survivors of intimate partner violence (IPV), and this includes not only the delivery of services, but also screening and evaluation materials. Given that Spanish is the most widely used language within the United States (U.S.) outside of English, it is important to ensure that measures of IPV are valid and reliable for use with Spanish-speaking survivors in the U.S. context. As such, the purpose of this study is to validate the Scale of Economic Abuse-12 for use with Spanish-speaking survivors. This study utilizes baseline data from 436 survivors of IPV who participated in a longitudinal, randomized controlled study evaluating a financial empowerment program. This included 201 participants that completed the survey in Spanish, and 235 participants that completed the survey in English. Confirmatory factor analysis (CFA) was used to test for measurement invariance across the Spanish and English language survey groups. After measurement invariance testing was completed, the reliability of the SEA-12 was examined for both groups. When examining the psychometric equivalence of the SEA-12 for both English and Spanish-speaking survivors of IPV, partial strict measurement invariance was achieved. The reliability of the scale and its subscales were also generally good. Results from this study demonstrated that the SEA-12 performed well with the Spanish-speaking survivors in this sample based in the U.S. As such, the Spanish translation of the SEA-12 can be recommended for use in research and practice with Spanish-speaking survivors within the U.S.